Digesta Justyniańskie księga pierwsza. Tłumaczenie Bartosz Szolc-Nartowski, Oficyna Wydawnicza WSHP im. Ryszarda Łazarskiego, Warszawa 2007, ss. 130 - Staniszewski, Maciej (Zeszyty Prawnicze, 2017)
Digesta Justyniańskie księga pierwsza. Tłumaczenie Bartosz Szolc-Nartowski, Oficyna Wydawnicza WSHP im. Ryszarda Łazarskiego, Warszawa 2007, ss. 130